Fostering Ethical Organizational Climate and Workplace Spirituality To Prevent Deviance and Misbehaviours at Workplace: Life Sciences - Kaur, MS Gurpreet; Chaturvedi, Prof (Dr)Vijit; Yadav, Dr DS (International Journal of Life Science and Pharma Research, 2023)
The objective of this research is to examine the role of workplace spirituality in reducing undesirable workplace behaviours. Organizational misbehaviour, as defined by Vardi and Wiener 1996 1, is any voluntary act by employees that violates fundamental organizational or society norms. Employee deviant behavior is defined as employee deliberate activity that breaches standard norms of the organization and endangers organizational well-being." Deviant misbehaviors that occur within the organization are often deemed as unethical deviations and sometimes develop due to environmental factors. Factors within the organizational environment such as organizational support, management support, role conflict, and work demand have been shown to be significant correlates of deviant behaviors. Deviations are often identified as responses to undesirable stimulus that elicits negative emotional state among employees. Additionally, it aims to investigate "ethical organizational climate" as a potential catalyst in enhancing the negative effects of workplace spirituality on unruly employee behaviours. Data was collected from 158 salespersons employed in private sector banking and insurance organizations and analysed using AMOS-SEM (structural equation modelling). The findings suggested that a direct positive relationship exists between workplace spirituality and ethical organizational climate. Also, ethical organizational climate exerted significant negative effects on salespersons deviant misbehaviours, thereby reducing them and acted as an overall mediator in the relationship between workplace spirituality and deviant misbehaviours among salespeople working in banking and insurance. The implications can help professionals working in the financial sectors in curbing deviant misbehaviours by embracing a more spiritual and ethical work culture for the benefit of their workers, their company, and the greater society. Thus, the research is novel to specifically focus on how workplace spirituality with a mediating effect of ethical work climate makes a difference.